Care of the Patient With Acute Ischemic Stroke (Posthyperacute and Prehospital Discharge): Update to 2009 Comprehensive Nursing Care Scientific Statement. Issue 5 (May 2021) - Green, Theresa L.; McNair, Norma D.; Hinkle, Janice L.; Middleton, Sandy; Miller, Elaine T.; Perrin, Stacy; Power, Martha; Southerland, Andrew M.; Summers, Debbie V.
Abstract : In 2009, the American Heart Association/American Stroke Association published a comprehensive scientific statement detailing the nursing care of the patient with an acute ischemic stroke through all phases of hospitalization. The purpose of this statement is to provide an update to the 2009 document by summarizing and incorporating current best practice evidence relevant to the provision of nursing and interprofessional care to patients with ischemic stroke and their families during the acute (posthyperacute phase) inpatient admission phase of recovery. Many of the nursing care elements are informed by nurse-led research to embed best practices in the provision and standard of care for patients with stroke. The writing group comprised members of the Stroke Nursing Committee of the Council on Cardiovascular and Stroke Nursing and the Stroke Council. A literature review was undertaken to examine the best practices in the care of the patient with acute ischemic stroke. The drafts were circulated and reviewed by all committee members. This statement provides a summary of best practices based on available evidence to guide nurses caring for adult patients with acute ischemic stroke in the hospital posthyperacute/intensive care unit. In many instances, however, knowledge gaps exist, demonstrating the need for continued nurse-led research on care of the patient with acute ischemic stroke.